2014
DOI: 10.1097/01.mib.0000442921.77945.09
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Disease Course of Early-onset Pediatric Inflammatory Bowel Disease

Abstract: BACKGROUND:\ud Early-onset (EO) pediatric inflammatory bowel diseases (IBD) seem to be more extensive than those with a later onset. To test this hypothesis, we examined the phenotype and disease course of patients with IBD diagnosis at 0 to 5 years, compared with the ranges 6 to 11 and 12 to 18 years.\ud METHODS:\ud Anatomic locations and behaviors were assessed according to Paris classification in 506 consecutive patients: 224 Crohn's disease, 245 ulcerative colitis, and 37 IBD-unclassified.\ud RESULTS:\ud E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
85
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 39 publications
23
85
3
Order By: Relevance
“…In those with CD, the rate of complicated behaviours [B2 or B3] was similar in both age groups in our study, which contrasts with Gupta et al's finding of a higher rate of complicated behaviours in those with IBD aged 6-16 years/ 17 Upper gastrointestinal location [L4] and anoperineal lesions were found to be similar in both age groups. The rate of L4 among those with VEO-CD [32%] was similar to that reported by Aloi et al 15 but much higher than that found by Heyman et al [5%]. 7 In those with UC, the rates of ulcerative proctitis [E1] and extensive colonic involvement [E3/E4] were similar in both age groups.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In those with CD, the rate of complicated behaviours [B2 or B3] was similar in both age groups in our study, which contrasts with Gupta et al's finding of a higher rate of complicated behaviours in those with IBD aged 6-16 years/ 17 Upper gastrointestinal location [L4] and anoperineal lesions were found to be similar in both age groups. The rate of L4 among those with VEO-CD [32%] was similar to that reported by Aloi et al 15 but much higher than that found by Heyman et al [5%]. 7 In those with UC, the rates of ulcerative proctitis [E1] and extensive colonic involvement [E3/E4] were similar in both age groups.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the time between the onset of symptoms and diagnosis was not delayed in the VEO-IBD group, whatever the type of IBD. As previously reported, 7,14,15,17,29,35 the initial presentation was different according to age group, with mucous bloody stools significantly more frequent in cases of VEO-IBD, probably because of the higher rate of isolated colonic disease in those with CD and a higher proportion of UC compared with older children. As noted by Gupta et al, 17 weight loss and abdominal pain were significantly more common in the EO-IBD group and this was also the case in our study.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations